Interactions between glycyl-L-phenylalanine and β-cyclodextrin from diffusion, spectroscopic and computational studies - Ramos, M. L. (2020)
The transport and association of the dipeptide glycyl-L-phenylalanine (Gly-L-Phen) in solutions containing cyclodextrins are of prime importance given its relevance in different areas, from biochemistry to wastewater treatment. We have investigated the interaction between aqueous Gly-L-Phen and β-cyclodextrin (β-CD) by NMR, DFT calculations in parallel with UV/visible absorption, luminescence spectral measurements and diffusion experiments. Ternary mutual diffusion coefficients of aqueous {Gly-L-Phen + β-CD} solutions have been measured by using the Taylor dispersion technique. The results show that the association of Gly-L-Phen and β-CD has a significant effect on the diffusion coefficients, consistent with an association constant of about 50 to 100, assuming a 1:1 (Gly-L-Phen):(β-CD) stoichiometry. This stoichiometry has been assessed by the continuous variation (Job's plot) method and the association constant was determined by using the Hildebrand-Benesi equation modified for NMR applications. The association constant was estimated to be equal to 40. This association constant is in close agreement with that obtained by fluorescence measurements (K = 43). Additionally, from NMR, detailed structural information on the complex has been obtained. This has been complemented by DFT and TD-DFT studies.